Studies on carbofuran and carbendazim residues in Piper betle leaves - and R. BANERJI, B.S. DIXIT, J.K. JOHRI (Indian Phytopathology, 2002)
The residue levels of carbamate pesticides viz. carbofuran and carbendazim applied to a betelvine crop were determined in order to estimate the safe use of betel leaves cv. Desawari for edible purposes. The residues of these pesticides were found to be below toxic levels after 60 days of treatment.